PERANCANGAN SISTEM INFORMASI E-COMMERCE PADA SALES AUTO 2000 CILEDUG - Yudi Yudi; Usman Gultom; Rachmawaty Haroen (Jurnal Manajamen Informatika Jayakarta, 2021)
Auto 2000 Ciledug is a company that sells various types of Toyota cars that are already competing in the global market. Through dialogue with those who use Toyota products, the company continues to acquire new knowledge and incorporate it into product development by contributing through product and service innovation, optimizing various work procedures at Car Dealers. With this information system, it is hoped that it will simplify and speed up the car sales process at Auto 2000 Ciledug. Such as, can access online applications, can place car orders, can simplify data management to produce reports. In the current Auto 2000 Ciledug running system, there are problems such as the application used cannot be ordered online. From the entire system that the author has created, it can be concluded that, with this information system, it is expected to simplify and accelerate the car sales process at Auto 2000 Ciledug, such as data management to report creation. This system is still not perfect, because there are still several processes that must be added, such as the process if the car is damaged / lost and the accounting process (financial calculations).